Seroprevalence of Mycoplasma synoviae in breeding turkeys reared in the Lima region, Peru - Nieves H., Mariela Nieves H. (2010)
The seroprevalence of Mycoplasma synoviae in breeder turkeys in Lima during 2007 was evaluated. Blood samples were collected in 400 breeder turkeys, older than 8 weeks of age and of both sexes, in the districts of Asia, Puerto Viejo and Chilca, Lima. Blood samples were analyzed by the ELISA technique to detect antibodies against M. synoviae. All samples were negative indicating that these birds were not exposed to the pathogen.